What Drives Participation in Online Cash Waqf? Integrating Religious, Social, and Technological Factors - Asmen Junaidi Firman; Irham Zaki; Rahmad Hidayat; Intan Diane Binangkit (Lan Tabur: JURNAL EKONOMI SYARIAH, 2026)
Online cash waqf has grown rapidly alongside the digitalization of Islamic philanthropy in Indonesia; however, public literacy, awareness, and participation remain relatively low compared to its national potential. This study positions itself within the behavioral and Islamic finance literature by examining key determinants of individuals’ intention to participate in online cash waqf. Specifically, it investigates the effects of religious motivation, Islamic financial literacy, subjective norm, awareness, and perceived ease of use. Employing a quantitative approach, this study analyzes survey data from 150 Indonesian Muslim respondents using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to test direct and indirect relationships, including mediation effects. The results indicate that subjective norm, awareness, and perceived ease of use have a significant positive influence on participation intention. Conversely, religious motivation and Islamic financial literacy do not have a direct effect; their influence is mediated through awareness and subjective norm. These findings demonstrate that social influence, cognitive awareness, and technological convenience play a more decisive role than religiosity or financial literacy alone. The study concludes that increasing participation in online cash waqf requires strengthened public education, improved digital platform usability, and community-based social campaigns, with practical implications for nazhir institutions and regulators.